Answer:
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Step-by-step explanation:
Given equation is ![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
Factor denominators then solve by making denominators equal
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![\frac{y\left(y+4\right)-4\left(y-4\right)}{\left(y-4\right)\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%7D%7B%5Cleft%28y-4%5Cright%29%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![y\left(y+4\right)-4\left(y-4\right)=9](https://tex.z-dn.net/?f=y%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%3D9)
![y^2+4y-4y+16=9](https://tex.z-dn.net/?f=y%5E2%2B4y-4y%2B16%3D9)
![y^2=9-16](https://tex.z-dn.net/?f=y%5E2%3D9-16)
![y^2=-7](https://tex.z-dn.net/?f=y%5E2%3D-7)
take squar root of both sides
![y=\pm \sqrt{-7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20%5Csqrt%7B-7%7D)
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Hence final answer is
.
<span>2/3 and 24/36 and 6/9
for 2/3 just dvide by 6, 24/36 just multiply both terms by 2 and for 6/9 just divide by 2</span>
The constant of proportionality is for every 1 x, there is 0.25 y. y = 0.25, and on a graph, x is always the "1." Since x is worth 1, y must be worth 0.25.
Answer:
9
Step-by-step explanation:
x-5+7=11
First think of what +7 = 11 then subtract by 5
check :)
Answer:
Not equivalent
Step-by-step explanation:
The three would also be distributed to z making the correct equivalent expression 15+3z